An Immune-Related Signature Predicted Survival in Patients With Kidney Papillary Cell Carcinoma - Shen, Junwen; Wang, Rongjiang; Chen, Yu; Fang, Zhihai; Tang, Jianer; Yao, Jianxiang; Ling, Yuhang; Zhang, Lisha; Zhang, Xu (Frontiers in Oncology, 2021)
Immune-related genes are important factors in tumor progression. The main aim of this study was to identify the immune-related genes in kidney papillary cell carcinoma (pRCC) patients. We downloaded RNAseq data and clinical information of pRCC patients from the TCGA database and retrieved the immune-related genes list from Immport. From the data, we mined out 2,468 differential expression genes (DEGs) and 183 immune-related DEGs. Four hub DEGs (NTS, BIRC5, ELN, and CHGA) were identified after conducting Cox analysis and LASSO analysis. Moreover, the prognostic value of the signature based on four hub DEGs was verified using Kaplan–Meier analysis (P = 0.0041 in the training set and p = 0.021 in the test set) and ROC analysis (AUC: 0.957 in 1 year, 0.965 in 2 years, and 0.901 in 3 years in the training set, and 0.963 in 1 year, 0.898 in 2 years, and 0.742 in 3 years in the test set). Furthermore, we found that the high-risk score group had a higher percentage of B cells in the immune component, a higher expression of immune-related genes (CTLA4, LAG3, PDCD1LG2, and TIGIT), and a better immunotherapy response.